Understanding the changing faculty workforce in higher education: A comparison of non-tenure track and tenure line experiences - Ott, Molly; Cisneros, Jesus (Education Policy Analysis Archives, 2015)
Non-tenure track faculty are a growing majority in American higher education, but research examining their work lives is limited. Moreover, the theoretical frameworks commonly used by scholars have been critiqued for reliance on ideologically charged assumptions. Using a conceptual model developed from Hackman and Oldham’s (1980) Job Characteristics Model (JCM) and prior research on faculty workplace experiences, this study considers the extent to which full-time non-tenure track and tenure line faculty share a professionalized approach to their jobs, working conditions, and how this is associated with their organizational commitment. Findings demonstrate important consistencies in full-time faculty views of their workplaces and jobs across appointment type. Satisfaction with resources, rewards, autonomy and feedback had a significant positive relationship with odds of organizational commitment for all faculty groups. Overall, the results suggest being removed from the tenure track is not associated with faculty viewing their jobs in a substantially different way than those in tenure line positions, which underscores the importance of conceptualizing full-time faculty work as an integrated whole.